Monetary policy and racial inequality in housing markets: A study of 140 US metropolitan areas - Qi Li; Xu Zhang (Bank of Canada, 2023)
This paper investigates the differential impact of monetary policy on homeownership and housing returns among Black, Hispanic and White households. Using data on 13 million repeat sales from 1993 to 2020, we construct and analyze race-specific entries and exits of homeownership and housing returns for 140 metropolitan areas in the United States. Our findings reveal significant heterogeneity: for minority households, one unit of monetary tightening leads to a 15% lower housing return and a 31% lower entry into homeownership than White households. This heterogeneity primarily stems from the less favorable labor market responses of minority groups to contractionary monetary policy. These findings emphasize the unintended consequences of monetary policy on racial inequality in the housing market.
Keywords: E52; E40; R00; 330; Central bank research; Housing; Monetary policy